Analysis and Design of an Ontology for Intensive Care Diagnoses - de Keizer, N. F.; Abu-Hanna, A.; Cornet, R.; Zwetsloot-Schonk, J. H. M.; Stoutenbeek, C. P. (Methods of Information in Medicine, 1999)
Information about the patient‘s health status and about medical problems in general, play an important role in stratifying a patient population for quality assurance of intensive care. A terminological system which supports both the description of health problems for daily care practice and the aggregation of diagnostic information for evaluative research, is desirable for description of the patient population. This study describes the engineering of an ontology that facilitates a terminological system for intensive care diagnoses. We analyzed the criteria for such an ontology and evaluated existing terminological systems according to these criteria. The analysis shows that none of the existing terminological systems completely satisfies all our criteria. We describe choices regarding design, content and representation of a new ontology on which an adequate terminological system is based. The proposed ontology is characterized by the explicit and formal representation of the domain model, the metaspecification of its concepts, the vocabulary to define concepts and the nomenclature to support the composition of new concepts.
Keywords: Ontology; Conceptual Modeling; Terminological System; Nomenclature; Intensive Care; Diagnosis